Introduction to machine learning - Alpaydin, Ethem (MIT Press, 2010)
The goal of machine learning is to program computers to use example data or past experience to solve a given problem. This is a comprehensive textbook on the subject, covering a broad array of topics not usually included in introductory machine learning texts.
Keywords: Machine learning.; elektronické knihy; electronic books